2009
DOI: 10.1007/s00268-009-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Value of Multidetector Row CT in the Assessment of Longitudinal Extension of Cholangiocarcinoma—Correlation Between MDCT and Microscopic Findings

Abstract: Although the cause of the difference between the hyperattenuated and hypoattenuated cholangiocarcinoma still is unclear, MDCT can be an alternative to direct cholangiography in selected patients with hyperattenuated cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 56 publications
(56 reference statements)
0
31
0
Order By: Relevance
“…However, precise diagnosis for tumor spreading along the proximal bile duct remains difficult, even with high-quality contrast-enhanced MDCT. [17][18][19][20][21] The most common reason for inaccuracy is underestimation of the extent of tumor, probably due to the presence of minimum invasive cancer without recognizable enhanced wall thickening on MDCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, precise diagnosis for tumor spreading along the proximal bile duct remains difficult, even with high-quality contrast-enhanced MDCT. [17][18][19][20][21] The most common reason for inaccuracy is underestimation of the extent of tumor, probably due to the presence of minimum invasive cancer without recognizable enhanced wall thickening on MDCT.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, the accuracy rate for proximal bile duct involvement is in the range of 77% to 92%. [17][18][19][20][21] Generally, MDCT tends to underestimate the proximal spread of tumors with respect to the pathological findings, probably due to the presence of a minimally invasive cancer and/or superficial invasion along the bile duct without recognizable enhanced wall thickening on MDCT. Ebata et al 22 previously demonstrated that the mean length of proximal superficial and intramural microscopic tumor spread from the macroscopic tumor margin was 14 mm and 4.6 mm, respectively.…”
mentioning
confidence: 98%
“…Before 2002, conventional catheter arteriography and percutaneous transhepatic portography 39 were performed to reveal vascular anatomy and to diagnose vascular invasion. 43 Other imaging approaches, including magnetic resonance imaging and positron emission tomography, were adopted in selected patients when needed. 43 Other imaging approaches, including magnetic resonance imaging and positron emission tomography, were adopted in selected patients when needed.…”
mentioning
confidence: 99%
“…2). 6 Lymphadenopathy was observed around the common hepatic artery, hepatoduodenal ligament, and peripancreatic head.…”
Section: Case Reportmentioning
confidence: 98%